The low-temperature phase of alpha-(BEDT-TTF)(2)KHg(SCN)(4) .2. Pressure dependence of the Shubnikov-deHaas oscillations - House, A; Lubczynski, W; Blundell, S; Singleton, J; Hayes, W; Kurmoo, M; Day, P (1996)
The magnetoresistance of α-(BEDT-TTF)2MHg(SCN)4 (where BEDT-TTF is bis(ethylenedithio)tetrathiafulvalene and M = NH4 or K) has been studied under pressures of up to 14.8 kbar and for temperatures down to 0.7 K. The ≃671 T (α) and ≃4270 T (β) Shubinkov-de Haas oscillations observed in the ambient pressure magentoresistence of α-(BEDT-TTF)2KHg(SCN)4 persist to the highest pressure while the other quantum oscillatory frequencies are removed under pressure. A strong second-harmonic component of the α-frequency oscillations is observed on the raw data at 1 bar and is initially suppressed by pressure but returns above ≃9 kbar. Furthermore, in the salt α-(BEDT-TTF)2NH4Hg(SCN)4 a similar pronounced second harmonic of the quantum oscillations has been observed at the highest pressures. The origins of these features of the data are discussed in the context of current models of the Fermi surfaces of these materials.